Lactobacillus acidophilus NCFM and Lactiplantibacillus plantarum Lp-115 inhibit Helicobacter pylori colonization and gastric inflammation in a murine model - Shen, Siqi; Ren, FeiFei; Qin, Haiming; Bukhari, Ihtisham; Yang, Jing; Gao, Dafang; Ouwehand, Arthur C.; Lehtinen, Markus J.; Zheng, Pengyuan; Mi, Yang (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose: To determine the role of Lactobacillus strains and their combinations in inhibiting the colonization of H. pylori and gastric mucosa inflammation.Methods: Human gastric adenocarcinoma AGS cells were incubated with H. pylori and six probiotic strains (Lactobacillus acidophilus NCFM, L. acidophilus La-14, Lactiplantibacillus plantarum Lp-115, Lacticaseibacillus paracasei Lpc-37, Lacticaseibacillus rhamnosus Lr-32, and L. rhamnosus GG) and the adhesion ability of H. pylori in different combinations was evaluated by fluorescence microscopy and urease activity assay. Male C57BL/6 mice were randomly divided into five groups (uninfected, H. pylori, H. pylori+NCFM, and treated with two lactobacilli strains for six weeks. H. pylori colonization and tissue inflammation statuses were determined by rapid urease test, Hematoxylin-Eosin (HE) staining, immunohistochemistry, and qRT-PCR and ELISA.